University students' level of boredom and their coping strategies in emergency remote education during the coronavirus pandemic - Solhi, Mehdi; Önen, Serap (Inderscience Enterprises Ltd., 2023)
The purpose of this study was twofold: firstly, we investigated whether there is a difference between male and female university students' level of boredom and their boredom coping strategies (i.e., cognitive approach, behavioural approach, cognitive avoidance, and behavioural avoidance) in emergency online lessons during the COVID-19 pandemic, and secondly an attempt was made to examine whether the participants' academic level (i.e., freshman, sophomore, junior and senior) affects their boredom experiences and boredom coping strategies. A total of 201 undergraduate students from a Turkish state university participated in the study. Results indicated that the male university students experience higher levels of boredom than their counterparts. In addition, the female participants exhibited stronger inclination towards using both cognitive approach and cognitive avoidance than the males to strategically cope with boredom. Besides, the participants with different academic levels did not score differently in their level of boredom and they indicated a significant difference only in their behavioural avoidance in coping with boredom. Indeed, as the academic level of the participants increases, they exhibit a greater tendency to use behavioural avoidance to relieve boredom.
Keywords: Academic Boredom; Boredom Coping Strategies; Emergency Online Lessons